2022
DOI: 10.3389/fmed.2022.819122
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Colorectal Cancer in Patients With Irritable Bowel Syndrome: A Meta-Analysis of Population-Based Observational Studies

Abstract: Background and AimsEvidence on the association between irritable bowel syndrome (IBS) and colorectal cancer (CRC) risk is inconsistent. Therefore, we aimed to examine whether IBS leads to an increased risk for CRC using a systematic review and meta-analysis approach.MethodsPubMed, Embase, and Web of Science were systematically searched to identify all relevant literature published through July 30, 2021. The pooled risk ratios (RRs) and corresponding 95% confidence intervals (CIs) for CRC after diagnosis of IBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…It is important to note that our results only illustrate a positive correlation between a history of H. pylori infection and the development of CRC and do not establish any direct causality. Moreover, despite the fact that the risk of developing CRC in patients with IBS is still controversial in the current literature [ 31 , 32 ], it is important to note that our study demonstrated a significantly elevated OR of 3.19 (95%CI 3.07-3.32).…”
Section: Discussionmentioning
confidence: 56%
“…It is important to note that our results only illustrate a positive correlation between a history of H. pylori infection and the development of CRC and do not establish any direct causality. Moreover, despite the fact that the risk of developing CRC in patients with IBS is still controversial in the current literature [ 31 , 32 ], it is important to note that our study demonstrated a significantly elevated OR of 3.19 (95%CI 3.07-3.32).…”
Section: Discussionmentioning
confidence: 56%
“…Additional file 4 : Table S3 displays the lower aHR of colorectal cancer for the colchicine users among the chronic colitis-(ulcerative colitis, Crohn’s disease) in young adult [ 9 , 18 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…IBS can cause several extraintestinal symptoms such as headache, tiredness, fibromyalgia and poor social functioning and emotional well-being [ 3 ]. Though IBS does not cause increased mortality or cancer incidence [ 4 ], the severity of the symptoms reduces the quality of life of the patients, which leads them to skip work or school, reducing their daily productivity and causing a financial burden to society [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%